Konflik Politik & Agama Dalam Film Cairo Conspiracy (Boy From Heaven) 2022 Karya Tarik Saleh - Wahyu Trisno Aji; Faizah harani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out and understand the political and religious conflicts in the film Cairo Conspiracy 2022. Cairo Conspiracy was first released at the Cannes Film Festival 2022. This film has a duration of 1 hour 33 minutes and is available in Indonesian. The film Cairo conspiracy or Boy From Heaven 2022 is a fictional story (made up) or not a real story or based on a true story. This film was written by Tarik Saleh who is a writer and director from Sweden, Egypt. The film Cairo Conspiracy or Boy From Heaven 2022 is a film that paints a gloomy picture of power taking place at one of the best and most magnificent Islamic universities in the world, namely the Al-Azhar Islamic University in Cairo, Egypt. The research method used in this research is qualitative, where qualitative research emphasizes analysis to obtain descriptive data results in the form of people's written or spoken words and observable behavior. and the type of research used is descriptive research with data analysis techniques in the form of content analysis